Apatinib in refractory radiation-induced brain edema: A case report. Issue 46 (November 2017) - Hu, Wei Guo; Weng, Yi Ming; Dong, Yi; Li, Xiang Pan; Song, Qi-Bin
Abstract: Rationale: Apatinib is a novel tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, which has observed to be effective and safe in refractory radiation-induced brain edema, like Avastin did. Till now, there is no case report after apatinib came in the market. Patient concerns: Two patients who received brain radiotherapy developed clinical manifestations of brain edema, including dizziness, headache, limb activity disorder, and so on. Diagnoses: Two patients were both diagnosed as refractory radiation-induced brain edema. Interventions: Two patients received apatinib (500 mg/day) for 2 and 4 weeks. Outcomes: Two patients got symptomatic improvements from apatinib in different degrees. Magnetic resonance imaging after apatinib treatments showed that compared with pre-treatment imaging, the perilesional edema reduced dramatically. However, the toxicity of apatinib was controllable and tolerable. Lessons: Apatinib can obviously relieve the symptoms of refractory radiation-induced brain edema and improve the quality of life, which offers a new method for refractory radiation-induced brain edema in clinical practices. But that still warrants further investigation in the prospective study.